Directors Remuneration and Tax Planning of Listed Companies - Mohd Waliuddin, Mohd Razali; Afizal Eizaz, Abdul Razak; Cheuk, Sharon Choy Sheung; Dyg Haszelinna, Abg Ali (AESS Publications, 2019)
Remuneration may be given in the form of incentives for the directors to engage in tax planning activity. The purpose of this study is to examine the relationship between directors’ remuneration and book tax differences (BTDs) as a proxy for tax planning. A sample of 500 Malaysian listed companies for the period of 2014-2016 were obtained and examined. Several control variables such as company size, leverage, capital intensity, and board size that have an impact on tax planning are used in this study.The directors’ remuneration and board size data were collected from annual reports and all remaining financial data were collected from Eikon DataStream. The results show that there is a positive significant relationship on directors’ cash remuneration on tax planning activity. Based on the findings, it is proven that directors’ remuneration is an important factor in motivating directors to engage in tax planning activity in the company. However, directors’ non-cash remuneration showed a negative significant relationship with tax planning. Non-cash remuneration may reduce directors’ interest in engaging with tax planning because it exposes risk of stock fluctuation in price in the market and increase agency costs to minority shareholders. All control variables significantly impact company tax planning as well. Suggested future research include the use of other tax planning variables such as permanent and temporary BTDs, and deferred tax assets.